Urgency of Maja Labo Dahu Local Wisdom Value in The Formation of Children's Religious Character in Rada Village - Nofitasari Nofitasari; A Gafar Hidayat; Nurnaningsih Nurnaningsih (Yupa: Historical Studies Journal, 2025)
This research is to examine the urgency of the local wisdom value of maja labo dahu in the formation of children's religious character in Rada village, Bima regency. Maja labo dahu, which means "shame and fear (of god)", is a philosophy of life of the Bima people that emphasizes the importance of shame to do wrong and fear of God as a moral foundation. This value is believed to be able to become a social control and shape the character of children who are honest, discilplind, responsible, and avoid reprehensible actions. This research uses a qualitative approach with a case study method, data collection techniques in the form of in-depth interviews, participatory observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation and coclusion drawing. The results showed that the integration of maja labo dahu values in the family environment plays an important role in instilling children's religious character. This value not only strengthens children's cultural and religious identity, but also becomes an effective moral fortress in facing the challenges of the digital era and the negative influence of social media. Thus, internalizing the value of maja labo dahu is urgent to strengthen the religious character of the younger amid rapid social change.